Preservation and storage of prepared ballistic gelatine. (February 2016) - Mattijssen, E.J.A.T.; Alberink, I.; Jacobs, B.; van den Boogaard, Y.
Highlights: A preservative does not significantly alter the penetration depth of projectiles. Storage of ballistic gelatine decreases the penetration depth of projectiles. After 4 weeks a significant effect is seen on the penetration depth of projectiles. Abstract: The use of ballistic gelatine, generally accepted as a human muscle tissue simulant in wound ballistic studies, might be improved by adding a preservative (Methyl 4-hydroxybenzoate) which inhibits microbial growth. This study shows that replacing a part of the gelatine powder by the preservative does not significantly alter the penetration depth of projectiles. Storing prepared blocks of ballistic gelatine over time decreased the penetration depth of projectiles. Storage of prepared gelatine for 4 week already showed a significant effect on the penetration depth of projectiles.